Study of the possibilities of physical therapy for patients with gonarthrosis associated with traumatic injury or prosthetics of the lower extremities - Kyrychenko, Yevgeniya; Antonova-Rafi, Yulia (The Ukrainian Scientific Medical Youth Journal, 2026)
the article provides an analytical review of effective physical therapy interventions for patients with knee osteoarthritis (OA) associated with traumatic injury or prosthetics. The feasibility of using the dual-task paradigm and kinesiotaping is substantiated. Based on the analysis of evidence-based sources, a comprehensive strategy for restoring function and improving the quality of life of patients is proposed.